2021
DOI: 10.19106/jmedsci005303202101
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokine (IL-6) and total count lymphocyte profiles in COVID-19 patients with different severity levels

Abstract: COVID-19 is caused by the SARS-CoV-2 infection that attacked the human respiratory system. In severe conditions, it causes pneumonia, kidney failure, acute respiratory distress syndrome (ARDS), and even death. The SARS-CoV-2 infection triggers the immune cells to secrete an excess of proinflammatory cytokines lead to cytokine storm. It is believed to become one of the mechanisms that cause the ARDS condition. The level of pro-inflammatory cytokines will differ with each case severity. This study aimed to evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…A cytokine storm damages the lungs, leading to ARDS and worsening the patient's clinical condition. 31 The analysis revealed that there was no significant difference in IL-6 levels between COVID-19 patients at Dr. M.…”
Section: Resultsmentioning
confidence: 89%
“…A cytokine storm damages the lungs, leading to ARDS and worsening the patient's clinical condition. 31 The analysis revealed that there was no significant difference in IL-6 levels between COVID-19 patients at Dr. M.…”
Section: Resultsmentioning
confidence: 89%